Cosmology of dewa ruci in the islamic tasawuf perspective - Ngatmin Abbas; Sukari; Faruq Alhabsi; Habib Assalam (Amorti: Jurnal Studi Islam Interdisipliner, 2024)
This study examines the cosmology of Dewa Ruci from the perspective of Islamic mysticism, focusing on faith, purity, and spiritual journey. The research aims to explore how the concept of Dewa Ruci in Javanese narratives relates to Islamic mysticism. To achieve this goal, the research method used is library research, involving the study of classical texts and literature related to Islamic mysticism as well as the stories of Dewa Ruci. The findings indicate that the cosmology of Dewa Ruci reflects harmony between Islam and Javanese culture, with Dewa Ruci symbolizing values. This study enhances our understanding of how Islamic teachings are conveyed through traditional narratives, enriching our understanding of Javanese cultural heritage and beliefs.